Fun/intoxication pre-drinking motives lead indirectly to more alcohol-related consequences via increased alcohol consumption on a given night. (March 2021) - Smit, Koen; Kuntsche, Emmanuel; Anderson-Luxford, Dan; Labhart, Florian
Highlights: Pre-drinking motives (PDM) and young adults' night-level drinking were examined. Fun/intoxication PDM were associated with alcohol use in drinking nights. Fun/intoxication PDM were indirectly associated with negative consequences. Conviviality and facilitation PDM were not associated with alcohol & consequences. Tailoring interventions based on PDM seems promising in preventing alcohol use. Abstract: Introduction: Pre-drinking increases alcohol use on drinking nights, which is associated with various adverse alcohol-related consequences but what motivates people to do so, i.e. the role of pre-drinking motives (PDM) in this link, is unclear. The current study examined a) the association of three PDM factors (fun/intoxication, facilitation, and conviviality) with average night-level alcohol use, b) whether PDM are associated with adverse alcohol-related consequences (hangover, drunk driving, blackout, risky sex, injury, and fights) and c) whether PDM mediates the link between night-level alcohol use and negative consequences. Methods: A sample of 204 young adult nightlife goers (48.8% males, Mage  = 19 SD = 2.4) from Switzerland reported PDM at baseline, and subsequently participated in a 2-month event-level study. Regressions models assessed direct and mediated associations. Results: Fun/intoxication PDM predicted alcohol use in subsequent drinking nights (11.3 nights per participant on average), but not the two other PDM. No direct link between PDM and consequences was found. However, fun/intoxication PDM lead indirectly to more adverse consequences through higher alcohol use. Conclusion: This study shows that predominantly 'fun/intoxication' predrinkers are at increased risk for alcohol consumption and consequences, but not those who predrink for conviviality or facilitation motives. The outcomes thus suggest the importance of specific PDM in preventing alcohol use for instance by tailoring interventions based on individuals' PDM in order to curb drinking and its associated consequences among young adults on weekend nights out.